Perioperative tislelizumab plus chemotherapy for locally advanced gastroesophageal junction adenocarcinoma (NEOSUMMIT-03): a prospective, nonrandomized, open-label, phase 2 trial - Run-Cong Nie; Shu-Qiang Yuan; Ya Ding; Yong-Ming Chen; Yuan-Fang Li; Cheng-Cai Liang; Mu-Yan Cai; Guo-Ming Chen; Wei Wang; Xiao-Wei Sun; De-Sheng Weng; Dan-Dan Li; et al. (Signal Transduction and Targeted Therapy)
Abstract This prospective, nonrandomized, open-label phase 2 trial (Chinese Clinical Trial Registry, ChiCTR2200061906) aimed to evaluate the effectiveness of adding the PD-1 antibody tislelizumab to perioperative chemotherapy in patients with locally advanced gastroesophageal junction adenocarcinoma (GEJA). This study enrolled patients with GEJA clinically staged as cT3-4aNanyM0 or cT1-2N+M0 from October 2022 to June 2023. Eligible patients were administered three preoperative and five postoperative 3-week cycles of treatment with PD-1 antibody tislelizumab plus SOX (S-1 and oxaliplatin) regimen. The primary endpoint was major pathological response (MPR) rate. Thirty-two patients were enrolled. The median age was 60 years (range: 28–74 years), and 53.1% (17/32) patients were Siewert III type. All patients received at least one cycle of assigned preoperative treatment, and 93.8% (30/32) patients completed three cycles of assigned preoperative tislelizumab and SOX. The R0 resection rate was 96.9% (31/32). MPR, pathological complete response (pCR) of primary tumors and ypT0N0 rates were 50.0% (16/32, 95% CI: 31.9–68.1%), 28.1% (9/32, 95% CI: 13.7–46.7%) and 25.0% (8/32, 95% CI: 11.5–43.4%), respectively. The surgical morbidity rate was 15.6% (5/32), and no 30-day mortality was observed. In the preoperative and postoperative treatment periods, the rate of treatment-related grade 3–4 adverse events was 31.2% (10/32). At the date of 7th Jan 2025, 8 (25.0%) patients occurred recurrence. Therefore, perioperative tislelizumab plus chemotherapy demonstrated significantly improved pathological regression and might be a promising option for patients with locally advanced resectable GEJA.